Establishment of National Economic Space: Jansen’s Urban Planning in South Anatolia - Karakaya, Emel (AESOP, 2012)
Following the İzmir Economy Congress of 1923, balanced distribution of economic development became a central spatial strategy of the Turkish government. Between 1923 and 1940, 117 urban plans were prepared for Turkish cities and towns. After the 1929 economic crisis, the principle of etatism reinforced the establishment of a national economic space through urban planning. Early development programmes identified regional foci for agricultural and industrial growth, particularly in southern Anatolia, including Adana, Ceyhan, Mersin, Tarsus, and Gaziantep. This study examines the relationship between the nation-building process and urban planning, focusing on the agricultural and industrial development region designed through Hermann Jansen’s plans. It explores how political concepts of nation-building translated into spatial planning, analysing the socio-spatial dynamics of Turkey’s early Republican period with emphasis on southern development initiatives.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: National economic space; Early Republican Turkey; Hermann Jansen; South Anatolia; nation-building process